Aptamer conjugated polydopamine-coated gold nanoparticles as a dual-action nanoplatform targeting β-amyloid peptide for Alzheimer's disease therapy. Issue 41 (12th October 2022) - Qin, Juan; Guan, Yanxue; Li, Zongjia; Guo, Xinyue; Zhang, Miaomiao; Wang, Dapeng; Tang, Jilin
Abstract : The accumulation and deposits of amyloid beta (Aβ) peptide are an important pathological hallmark of Alzheimer's disease (AD). Abstract : The accumulation and deposits of amyloid beta (Aβ) peptide are an important pathological hallmark of Alzheimer's disease (AD). The development of multifunctional agents that can effectively clear Aβ aggregates is one of the potential strategies to treat AD. Herein, aptamer conjugated polydopamine-coated gold nanoparticles (Au@PDA-Apt NPs) for targeting Aβ1–40 peptides were designed. Au@PDA-Apt NPs exhibited a strong capability to inhibit Aβ1–40 monomer fibrillization and disaggregate mature Aβ1–40 fibrils. In addition, Au@PDA-Apt NPs could effectively alleviate Aβ1–40 -triggered cytotoxicity. Importantly, AFM quantitative nanomechanical measurements indicated that Au@PDA-Apt NPs could prevent cell membrane damage and decrease of cell mechanical properties caused by Aβ1–40 aggregation. Taken together, this study provided a new dual-action nanoplatform for Aβ-targeted AD therapy.